Open borders, transport links and local labor markets - Olof Åslund; Mattias Engdahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
We study the labor market impact of opening borders to low-wage countries. The analysis exploits time and regional variation provided by the 2004 EU enlargement in combination with transport links to Sweden from the new member states. The results suggest an adverse impact on earnings of present workers in the order of 1 percent in areas close to pre-existing ferry lines. The effects are present in most segments of the labor market but tend to be greater in groups with weaker positions. The impact is also clearer in industries which have received more workers from the new member states, and for which across-the-border work is likely to be more common. There is no robust evidence on an impact on employment or wages. At least part of the effects is likely due to channels other than the ones typically considered in the literature.
Keywords: J16; J31; J61; 330; migration policy; immigration; labor market outcomes; Freizügigkeit; Arbeitsmigration; Arbeitsmigranten; Lohnniveau; Geographische Entfernung; EU-Staaten; Schweden